Screenwriting: Creative labor and professional practice - Conor, Bridget (Routledge, 2014)
Screenwriting: Creative Labor and Professional Practice analyzes the histories, practices, identities and subjects which form and shape the daily working lives of screenwriters. Author Bridget Conor considers the ways in which contemporary screenwriters navigate and make sense of the labor markets in which they are immersed. Chapters explore areas including: Screenwriting histories and myths of the profession Screenwriting as creative labor Screenwriters’ working lives Screenwriting work and the how-to genre Screenwriting work and inequalities Drawing on historical and critical perspectives of mainstream screenwriting in the USA and UK, as well as valuable interviews with working screenwriters, this book presents a highly original and multi-faceted study of screenwriting as creative labor and professional practice. The Open Access version of this book, available at www.taylorandfrancis.com, has been made available under a Creative Commons Attribution-NonCommercial-No Derivatives 4.0 license.https://www.taylorfrancis.com/books/9780203080771